2021
DOI: 10.1093/ecco-jcc/jjab076.388
|View full text |Cite
|
Sign up to set email alerts
|

P262 Effectiveness and safety of ustekinumab in elderly patients: Real world evidence from ENEIDA registry

Abstract: Background Clinical trials and real-life studies with Ustekinumab in Crohn’s disease show its good efficacy and safety profile. However, there are hardly any data on elderly patients, who are excluded from these clinical trials. Our aim is to evaluate these variables in real-life practice. Methods Retrospective analysis of patients from the prospectively maintained ENEIDA registry treated with Ustekinumab for Crohn’s disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In a previous cohort study of 103 vedolizumab-treated patients, 17% of patients developed a serious infection (13.8% in our cohort) [ 17 ]. In a Spanish cohort of 212 ustekinumab-treated elderly patients, a serious infection rate of 7% was reported [ 20 ] which is similar to our cohort. The magnitude of risk also appears broadly comparable to that reported for anti-TNF agents among elderly patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In a previous cohort study of 103 vedolizumab-treated patients, 17% of patients developed a serious infection (13.8% in our cohort) [ 17 ]. In a Spanish cohort of 212 ustekinumab-treated elderly patients, a serious infection rate of 7% was reported [ 20 ] which is similar to our cohort. The magnitude of risk also appears broadly comparable to that reported for anti-TNF agents among elderly patients.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, a single-centre cohort study from the USA reported response rates in excess of 90% in an elderly cohort of 39 patients but importantly remission was only achieved in 28% of patients [ 19 ]. Similarly, in the recently published Spanish cohort of 212 elderly patients, the week 54 response rate was 70% [ 20 ]. These differences are likely explained by differences in patient populations—for instance, in our cohort we had a lower proportion of patients with penetrating phenotype (13% vs 44% in the US study) and a greater proportion of smokers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Ustekinumab, a humanized monoclonal antibody, was shown by a study that it achieved clinical response in almost threequarters of elderly patients, with the same rate of infections and other adverse effects, with the exception of de novo neoplasms [14].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%